Relationship between Nutritional Status and Postoperative Outcomes of Breast Cancer - Ismawardany Imran, Andi; Bamahary, Aryanti R.; Pratama, Ahmad Ardhani; Purnamasari, Reeny; Latief M, Shofiyah; Sakti, Dachlia Sri (Newinera Publisher, 2024)
Breast cancer is the most common cancer in the world which is expected to increase morbidity and mortality rates . Nutritional status is an indicators that can be used to predict post-operative breast cancer outcomes . Breast cancer patients with poor / more nutritional status has a higher risk of experiencing more post-operative complications . This study was conducted to determine the nutritional status with post-operative outcomes in breasts Cancer patients. To determine the relationships between nutritional status (BMI) and post-operative outcomes in breast cancer patients at the Ibnu Sina Hospital Makassar. This study is cross -sectional analytic study, using a total sampling method with a total of 55 samples from patients medical records . Data analysis used the Chi- square test to assess whether there was a relationship. Obtained a significant relationships between nutritional status and length of stay (p = 0.002), and lymphedema (p = 0.027). While the relationships between nutritional status and post-operative wound complications was obtained (p = 0.052), .” history (p = 0.171). There is a relationships between nutritional status and post-operative outcomes for breasts Cancer.